Combining 68Ga-PSMA-PET/CT-Directed and Elective Radiation Therapy Improves Outcome in Oligorecurrent Prostate Cancer: A Retrospective Multicenter Study - Kirste, Simon; Kroeze, Stephanie G. C.; Henkenberens, Christoph; Schmidt-Hegemann, Nina-Sophie; Vogel, Marco M. E.; Becker, Jessica; Zamboglou, Constantinos; Burger, Irene; Derlin, Thorsten; Bartenstein, Peter; Ruf, Juri; la Fougère, Christian; et al. (Frontiers in Oncology, 2021)
Background In case of oligo-recurrent prostate cancer (PC) following prostatectomy, 68Ga-PSMA-PET/CT can be used to detect a specific site of recurrence and to initiate metastasis-directed radiation therapy (MDT). However, large heterogeneities exist concerning doses, treatment fields and radiation techniques, with some studies reporting focal radiotherapy (RT) to PSMA-PET/CT positive lesions only and other studies using elective RT strategies. We aimed to compare oncological outcomes and toxicity between PET/CT-directed RT (PDRT) and PDRT plus elective RT (eRT; i.e. prostate bed, pelvic or paraaortal nodes) in a large retrospective multicenter study. Methods Data of 394 patients with oligo-recurrent 68Ga-PSMA-PET/CT-positive PC treated between 04/2013 and 01/2018 in six different academic institutions were evaluated. Primary endpoint was biochemical-recurrence-free survival (bRFS). bRFS was analyzed using Kaplan–Meier survival curves and log rank testing. Uni- and multivariate analyses were performed to determine influence of treatment parameters. Results In 204 patients (51.8%) RT was directed only to lesions seen on 68Ga-PSMA-PET/CT (PDRT), 190 patients (48.2%) received PDRT plus eRT. PDRT plus eRT was associated with a significantly improved 3-year bRFS compared to PDRT alone (53 vs. 37%; p = 0.001) and remained an independent factor in multivariate analysis (p = 0.006, HR 0.29, 95% CI 0.12–0.68). This effect was more pronounced in the subgroup of patients who were treated with PDRT and elective prostate bed radiotherapy (ePBRT) with a 3-year bRFS of 61% versus 22% (p <0.001). Acute and late toxicity grade ≥3 was 0.8% and 3% after PDRT plus eRT versus no toxicity grade ≥3 after PDRT alone. Conclusions In this large cohort of patients with oligo-recurrent prostate cancer, elective irradiation of the pelvic lymphatics and the prostatic bed significantly improved bRFS when added to 68Ga-PSMA-PET/CT-guided focal radiotherapy. These findings need to be evaluated in a randomized controlled trial.